1997
DOI: 10.1177/030802269706000106
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Diversity in Glasgow, Part 1: Are We Meeting the Challenge?

Abstract: Ninety-four respondents returned selkompletlon questionnaires. Their level of contact, language and Information services, self-rated awareness, actual knowledge of cultural factors and attitudes towards the service provision to clients of Indian subcontinent origins (ISO) were Investigated. The respondents tended to self-rate their awareness as quite low. Knowledge about cultural factors was Influenced more by the therapist's age and source of knowledge than by whether he or she worked In an area with a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Cultural competence, as perceived by occupational therapists, has been documented in the occupational therapy literature (Khamisha, 1997;Phipps, 1995;Scott, 1997). It is reflected in how successfully therapists incorporate their cultural knowledge, previous experience, and awareness of different cultures into practice.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural competence, as perceived by occupational therapists, has been documented in the occupational therapy literature (Khamisha, 1997;Phipps, 1995;Scott, 1997). It is reflected in how successfully therapists incorporate their cultural knowledge, previous experience, and awareness of different cultures into practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kinebanian and Stomph (1992) found that occupational therapists tend to view clinical experiences from their own personal and professional cultural experiences. Occupational therapists therefore need to take time to analyse their own personal and professional values and beliefs (Khamisha, 1997), so that their own cultural background and subsequent interpretation of clients' behaviours do not impact negatively on the appropriateness or effectiveness of a service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results for sections 1-5 of the questionnaire were presented in part 1 of this article (Khamisha, 1997). The results for section 6 are presented here.…”
Section: Resultsmentioning
confidence: 99%
“…A fuller version of the method is available in part 1 of this article (Khamisha, 1997). The total population of practising occupational therapists employed within the city of Glasgow was targeted during a 3-week period.…”
Section: Summary Of Methodsmentioning
confidence: 99%
“…In the Netherlands, Kinébanian and Stomph (1992) interviewed Dutch practitioners about approaches they used to treat immigrant clients. The research of Khamisha (1997aKhamisha ( , 1997b focused on British therapist's cultural knowledge and service delivery to clients of Indian subcontinent origin. These studies all focused more on delineating barriers to the provision of culturally competent care than on defi ning the process of providing such care.…”
Section: Examination Of Cultural Competency In Occupational Therapymentioning
confidence: 99%